2017
DOI: 10.21660/2017.30.2583
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Haccp Implementation in Agricultural Food Products in Thailand

Abstract: Agricultural food industry in Thailand generated incomes about 10.5% gross domestic product (GDP) of the country in 2015. The demands of agricultural food products around the world has been increased for years. Agricultural food products from Thailand could not be exported as many as the growth of market demands because of the limitation of food safety guarantees. Analysis and Critical Control Points (HACCP) is a minimal requirement for exported food products to assure food safety. Not all Thai companies in ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…An important negative factor is the lack of understanding of the HACCP system by the management and personnel of food enterprises, the relatively high cost of developing and implementing this system, as well as the need to improve methodological guidelines for its application. [28,29,32,33]. It should also be noted that in recent decades, many food safety schemes have emerged around the world.…”
Section: Haccp System (Hazard Analysis and Critical Control Point) An...mentioning
confidence: 99%
“…An important negative factor is the lack of understanding of the HACCP system by the management and personnel of food enterprises, the relatively high cost of developing and implementing this system, as well as the need to improve methodological guidelines for its application. [28,29,32,33]. It should also be noted that in recent decades, many food safety schemes have emerged around the world.…”
Section: Haccp System (Hazard Analysis and Critical Control Point) An...mentioning
confidence: 99%
“…Similar finding from the study by Maldonado-Siman, Bai, Ramírez-Valverde, Gong, & Rodríguezde Lara, where it was found that the first motivation for Mexican meat enterprises to implement HACCP is for access to new foreign markets 30 . Kingphadung & Choothian did mention that for food products to be export to other countries, it requires food safety certifications, such as HACCP and ISO 22000 31 .…”
Section: The Motives Of Haccp Implementationmentioning
confidence: 99%
“…Findings from other studies also show the same as most of the employees in the food production companies lack knowledge of the HACCP system 33,34 . Lack of employee commitment and engagement in HACCP implementation is the most concerned as the barrier 23,31 . According to HACCP requirements, companies must develop guidelines for all processes and must control all the productions processes to meet the HACCP requirements.…”
Section: The Motives Of Haccp Implementationmentioning
confidence: 99%
See 1 more Smart Citation